(untitled) (Research, Society and Development, 2021)
The Neonatal Intensive Care Unit is responsible for newborns from 0 to 28 days that are severe or potentially serious, given that it has a specialized structure and team to provide the necessary life support. For parents, this environment is stressful and the team does not always prepare them for child care. Thus, the objective was to understand the perception of the family regarding nursing care for newborns in the Neonatal Intensive Care Unit. This is a field study, with a qualitative approach, carried out in a secondary care hospital of the public health network, carried out between January and June 2021 with ten relatives of newborns admitted to the unit, through of semi-structured interviews and so, according to the speeches, three thematic categories were delimited to be analyzed. The statements showed the difficulty of effective communication in the professional-family relationship, the lack of identification of the nurse, failures in health education and preparation for hospital discharge. Therefore, it is concluded that the family has a good perception about nursing care, but that there are still conditions to be improved for a broad and humanized care.